2020
DOI: 10.2337/db20-720-p
|View full text |Cite
|
Sign up to set email alerts
|

720-P: Prurigo Pigmentosa: An Acute Complication of Ketogenic Diet

Abstract: A 22-year old female with type 1 diabetes (T1DM) presented with generalized rash. She was diagnosed at the age of 9 years and is treated with insulin pump and CGMS (continues glucose monitoring sensors), her recent HbA1c was 7.4%. Four weeks prior to her rash presentation she started a low carbohydrate diet (50 gr of carbs per day) in order to improve her glycemic control. Pruritic erythematous papules, papulovesicular, and vesicles appeared on her axillary region, upper back and groins. Lesions were associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In a case series of nine patients, Goh et al 11 found that 33.3% of their cases were on KD before PP appearance. Furthermore, several other cases have reported the induction of PP following KD commencement with a satisfactory improvement of the lesions following the reintroduction of carbohydrates 7,11–23 . In total, we reviewed 22 cases of PP manifested following KD including two cases among our patients.…”
Section: Ref No Age/gender Duration Of Diet Before Pp Onset (Day) Tre...mentioning
confidence: 99%
See 1 more Smart Citation
“…In a case series of nine patients, Goh et al 11 found that 33.3% of their cases were on KD before PP appearance. Furthermore, several other cases have reported the induction of PP following KD commencement with a satisfactory improvement of the lesions following the reintroduction of carbohydrates 7,11–23 . In total, we reviewed 22 cases of PP manifested following KD including two cases among our patients.…”
Section: Ref No Age/gender Duration Of Diet Before Pp Onset (Day) Tre...mentioning
confidence: 99%
“…International Journal of Dermatology 2022, 61, 779-782 reintroduction of carbohydrates. 7,[11][12][13][14][15][16][17][18][19][20][21][22][23] In total, we reviewed 22 cases of PP manifested following KD including two cases among our patients. Most of the patients were female (18/22; 81.8%) with an average age of 24.9 years old.…”
mentioning
confidence: 99%